Pengembangan Sistem Informasi Monitoring Project berbasis Web menggunakan API Trello (Studi Kasus: CV. Kisah Kita Event Organizer) - Azzahra Princessa Shekina Wijaya; Issa Arwani; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
CV. Kisah Kita Event Organizer is a company engaged in services in organizing events in a professional manner. In running business processes, companies still do it manually by inputting data into Google Sheets in the ongoing project monitoring process. This causes problems such as not optimal service due to human error and requires excessive time estimation. From the urgency of the problem, we need a system that can monitor the project and provide convenience in data documentation. The system is integrated with the Trello API to make it easier for users. The analysis and design carried out on this system obtained 17 functional requirements and one non-functional requirement. Then modeled in the form of use cases, activity diagrams, sequence diagrams, class diagrams, physical data models and user interface design. Then it is implemented into a project monitoring information system that implements the Laravel framework with the Trello API. And tested using the Traceability Matrix test to track the suitability of the system design with the results that all functionality of the system is in accordance with the design that has been designed. Then tested using the Blackbox testing method in the form of testing the validity of the functional system when it is run and getting the system results as expected. For non-functional testing, use the Sortsite tool and the system results can be accessed through several web browsers.